“Blue Innovation” Pendampingan tata Kelola Kawasan Maritim Melalui Hilirisasi Produk Unggulan Desa Puger Kulon Guna Sustainability Ekonomi Desa - Mulyono, Resha Dwi Ayu Pangesti; Andriana, Andriana; Putra, Hendrawan Santosa; Kurrohman, Taufik; Indriatmiko, Pungki (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Puger Kulon Village demonstrates exceptional potential in the fisheries sector, offering significant opportunities for community economic enhancement. The diversity of fishermen's catches positions the village as a prospective center for sustainable fisheries product downstream processing. Nevertheless, limited human resource awareness regarding downstream processing concepts and insufficient management of fisheries economic zones constitute primary barriers to development. The objective of this community service program is to provide assistance in maritime area governance through downstream processing of superior products to strengthen sustainable village development using blue economy principles. The implementation stages encompass maritime area governance mapping, development of participatory coastal management options involving multiple stakeholders (residents, village government, tourism awareness groups, village-owned enterprises, and private sector), and enhancement of human resource competencies in processed fishery product creation and branding strategies. The anticipated outcome is the establishment of maritime area governance in Puger Kulon Village that effectively utilizes existing potential.